4,4′-Dimethoxy-2,2′-[methylazanediylbis(methylene)]diphenol - Veranitisagul, Chatchai (International Union of Crystallography, 2012)
The title compound, C(17)H(21)NO(4), shows an intramolecular hydrogen bond between a phenol OH group and the N atom. In the crystal, molecules are connected by pairs of O—H⋯O hydrogen bonds into inversion dimers.